East Asia and the Pacific Region Urban Sanitation Review : A Call for Action - World Bank (Washington, DC, 2014)
This study summarizes the main challenges to scaling up access to sustainable sanitation services in the urban areas of three countries in the East Asia and Pacific region-Indonesia, Philippines and Vietnam-and proposes the main steps these countries need to take to redress the status quo. The report is divided into four chapters. The first chapter provides an overview of the current level and quality of access to urban sanitation in the region. The second chapter examines the causes leading to the current state of urban sanitation, using four thematic areas: people, technology, institutions and finance. The third chapter identifies those factors that need to be in place to trigger a different way of doing business in the sector and that may ultimately lead to transformational changes. The final chapter proposes recommendations on how countries can upgrade and scale up urban sanitation services.